Optimalisasi TikTok Marketing Berbasis Psikologi Konsumen dalam Meningkatkan Niat Beli Ulang pada UMKM Ridho Snack. - Rindy Salsabila Anggieliani Irawan; Nena Dwi Cahya Maulidina; Alya Nur Afifah; Meisya Putri Syahrani; Tasya Augustiya (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
This community service activity aims to improve promotional effectiveness and strengthen the brand image of the "Ridho Snack" MSME through optimizing digital marketing based on a consumer psychology approach. Problems faced by partners include the suboptimal use of social media as a marketing communication tool, inconsistent digital content development, and unclear market segmentation. The activity was carried out through field observations, discussions and interviews with business owners, and gathering consumer input through online questionnaires to obtain insights into customer perceptions, preferences, and satisfaction levels. Based on the results of the problem identification, the implementation team provided assistance in reformulating the target market, preparing content planning, developing creative content based on customer testimonials on the TikTok platform, and strengthening marketing messages that emphasize product quality and hygiene. The results of the activity showed an increase in the professionalism of social media displays, more structured promotional communications, and increased brand awareness. This community service program contributes to encouraging the digital transformation of MSMEs as an effort to continuously increase business competitiveness in the era of technology-based marketing.